Urban groundwater development and management for metropolitan areas in South Africa-case study: Gautrain tunnel - Mahlahlane, Kgotso Caswell (University of the Free State, 2019)
Urbanization is a predominant challenge for urban groundwater management in most Metropolitan Municipalities (MMs) in South Africa. Most urban areas comprise of high-yielding aquifers, with sufficient potential to expand water supply incrementally and reduce the dependence on the existing municipal water supply system (Foster, 2013). The study assessed the status quo of urban groundwater management in four (4) MMs, namely; The City of Johannesburg (CoJ), City of Tshwane (CTMM), Ekurhuleni (EMM), and eThekwini (eTMM) to improve urban groundwater management practices and implement strategies to ensure the resource is protected and sustainable. MMs are using groundwater resources to varying degrees. However, groundwater makes up a small percentage of the total supply, reaching 6% in Tshwane. Additionally, treated acid mine drainage (i.e. rebounding groundwater) is added to the Vaal River System (VRS), making up to 3% of the current supply to the MMs in Gauteng. The overarching findings from the assessment are that groundwater use and management are poorly integrated into the key planning processes at the MMs. In no cases is there a coherent plan for groundwater development and management evident from the MMs and no such plan is integrated across each of the necessary and available planning documents. In light of the findings, we propose that groundwater development be planned and budgeted for in the Integrated Development Plans and protection of groundwater be strengthened within the Spatial Development Framework and Water Sensitive Design in the respective MMs. The findings further underpinned gaps that led to the identification of an urban groundwater challenge (excess ingress of groundwater into the Gautrain Tunnel) that could be solved by the development of innovative technical solutions. Currently, a total of 3.1 million m3/annum ingress groundwater is dewatered and discharged from 3 of the 5 localities. The discharge is mainly at Shaft E21, Shaft E7, and Sandspruit Discharge Point while discharge at Shafts E3 and Shaft E4 is unknown due to continuously low discharge rates (and are thus considered negligible). The inference from the average discharge volumes between 2013 and 2017 confirmed that 68% of the total groundwater is discharged from E2, 17% from E7 and 15% from Sandspruit Point. Of these points, only the Sandspruit Point discharges directly into the Sandspruit River and the remainder discharge into stormwater systems. Notwithstanding the combined discharge volume making up to 0.3% of the CoJ annual water demand, it remains a significant amount as CoJ faces a projected water deficit by 2030 (DWAF, 2009b). We, therefore, argued that a by-law prohibiting the discharge of groundwater from the tunnel with no beneficial use must be established. In instances where ingress groundwater will not be utilized for any bulk supply, active management is still a requirement to protect and conserve the resource. Based on the significant volume and generally good to excellent water quality (with few cases of elevated salt concentrations requiring minimal treatment) suitable for all uses, including human consumption, the following were beneficial uses identified for the available groundwater emanating from Shaft E2, Shaft E7 and the Sandspruit Discharge Point: (i) Decentralized Supply, (ii) Aquatic and Groundwater-dependent Ecosystem Augmentation, (iii) In-House use2, (iv) Augmenting Existing Bulk Water Systems, and (v) Bottling of the Water to Generate Revenue. The Pre-Feasibility Analysis was undertaken in terms of benefits, financial costs and legislative requirements with each scenario proving to be economically feasible with return on investments. In conclusion, the benefits and opportunities from the current study, particularly the Pre-Feasibility Analysis, were fully recognized and contributed to a shift from inadequate management of groundwater resources in urban areas with no beneficial use, to active management leading to the potential for bulk water supply.
Dissertation (M.Sc. (Geohydrology))--University of the Free State, 2019
Keywords: Urban groundwater management; Groundwater ingress; Innovative technical solutions; Gautrain tunnel; Urbanization; Metropolitan municipalities - South Africa